Komunikasi Organisasi dalam Proses Pembentukan Budaya Organisasi Melalui Agent Of Change - Syafitri, Verdania Puri; Toni, Ahmad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Organizations culture have a significant impact on the performance and success of an organization, and cultural change is often necessary to deal with evolving challenges. The purpose of this study is to investigate how effective organizational communication can shape adaptive and innovative organizational culture through change agents. This study aims to determine the important role of organizational communication in the process of forming organizational culture through the role of change agents (Agents of Change). The research method used is a qualitative descriptive method by analyzing documents and observing in organizations that experience cultural change. The collected data is systematically analyzed to identify the role of organizational communication in shaping the new organizational culture. The results show that open, inspiring, and ongoing organizational communication plays a key role in communicating the vision of change, explaining the reasons behind change, and facilitating constructive dialogue throughout the organization. Effective communication also supports the education and training of employees, engages them in change, and sustains the cultural change that has been achieved. Thus, this study highlights the importance of organizational communication in shaping an adaptive and innovative organizational culture through change agents.